CAMAC based multi spectrum scaling software for yield and half-life measurements - Akcali, Oezguer (AMER INST PHYSICS, 2007)
We have developed a graphical user interface (GUI) based on KmaxNT software whereby a CAMAC system is controlled over Windows 2000 operating system for multi-parametric data acquisition (DAQ). This system has enabled easy DAQ operations, control of SAMES T-400 neutron generator and fast pneumatic sample transport system (FSTS) with predefined irradiation, cooling and counting times. The overall counting time should be divided into periodic or variable intervals. This system is now in practical use for measurement of (n,f) reactions at Cekmece Nuclear Research and Training Center.
Keywords: CAMAC; GUI; data acquisition; Physics